Metal-induced oxidative stress in terrestrial macrolichens - Kováčik, Jozef; Dresler, Sławomir; Peterková, Viera; Babula, Petr (Chemosphere, 2018)
Short-term (24 h) responses of Cladonia arbuscula subsp. mitis and Cladonia furcata to copper (CuII) or chromium (CrIII) excess (10 or 100 μM) were compared. C. arbuscula accumulated more Cu and Cr at higher metal doses but both species revealed depletion of K and/or Ca amount. Not only Cu but also Cr typically elevated reactive oxygen species (ROS) formation (fluorescence microscopy detection of total ROS and hydrogen peroxide) and depleted nitric oxide (NO) signal, with Cu showing more negative impact on lipid peroxidation (BODIPY 581/591 C11 staining reagent). Metals and staining reagents also affected anatomical responses and photobiont/mycobiont visibility. Principally different impact of Cu and Cr was observed at antioxidative metabolites level, indicating various ways of metal-induced ROS removal and/or metal chelation: Cu strongly depleted glutathione (GSH) and stimulated phytochelatin 2 (PC2) content while ascorbic acid accumulation was depleted by Cu and stimulated by Cr. Subsequent experiment with GSH biosynthetic inhibitor (buthionine sulfoximine, BSO) revealed that 48 h of exposure is needed to deplete GSH and BSO-induced depletion of GSH and PC2 amounts under Cu or Cr excess elevated ROS but depleted NO. These data suggest close relations between thiols, NO and appearance of oxidative stress (ROS generation) under metallic stress also in lichens.
Keywords: Ascorbic Acid; Hydrogen Peroxide; Chromium; Antioxidants; glutathion; oxidační stres; Glutathione; Metals; Oxidative Stress; peroxid vodíku; Buthionine Sulfoximine; Reactive Oxygen Species; kovy; měď; lišejníky; Copper; peroxidace lipidů; Lipid Peroxidation; chrom; Environmental Pollutants; Phytochelatins; antioxidancia; Lichens; kyselina askorbová; reaktivní formy kyslíku; buthionin sulfoximin; látky znečišťující životní prostředí; fytochelatiny